Interview with Longterm Editor-in-Chief of Knygotyra, Professor Domas Kaunas (Full Member of the Lithuanian Academy of Sciences) - Navickienė, Aušra (Knygotyra, 2020)
Knygotyra (“Book Science”) is one of the longest existing scholarly journals among the periodicals published by Vilnius University. It has been in print since 1961. Until 1969, it was published under the title Bibliotekininkystės ir bibliografijos klausimai (“Issues of Librarianship and Bibliography”). During 1981–1991, as part of the series “Research Work of the Higher Education Institutions of the Lithuanian SSR,” it appeared in two volumes: one devoted to the problems of book history, publishing and distribution, and the other – to issues of libraries, bibliography, and information science. In 1990, the first volumes were turned into Knygotyra, a serial published by Vilnius University, while the second volumes were published independently under the title Informacijos mokslai (“Information Sciences”). Since 2003, Knygotyra has been regularly published twice a year as a scholarly journal. For decades, it has been referred to in Lithuanian and international databases as an open access, peer-reviewed journal and, since 2018, it is included into the Elsevier Scopus database. Domas Kaunas is the most experienced member of the Editorial Board and has been an Editor-in-Chief till 2019. Docent Genovaitė Raguotienė had been in this position for three years (1970‒1973), Professor Levas Vladimirovas – for fifteen years (1974‒1989), when Domas Kaunas subsequently joined the editorial board in 1979 and served as the Editor-in-Chief for three decades.